Search code examples
boolean-logicboolean-algebra

Boolean Algebra with Max terms


I want to simplify the following expression: F = (A+B+C)(A+B'+C)(A'+B+C)

I have simplified it accordingly.

F = (A+B+C)(A+B'+C)(A'+B+C)

F = (A+C)(A'+B+C)

F = AA' + AB + AC + A'C + BC + C

F = AB + C(A + A' + B + 1) = AB + C

However, the correct answer is (A+C)(B+C). Where in my "current" proof am I going wrong? I have seen the solution, but I want to know why my current approach is wrong.


Solution

  • Nothing wrong - it's just two different ways of expressing the same thing.

    If the goal is minimization I would argue that your solution is "better" since it only references each term once.

    Wolfram Alpha is your friend in cases like this.